EFEKTIVITAS MANGANESE GREENSAND DENGAN VARIASI DIAMETER DAN KETEBALAN MEDIA DALAM MENGURANGI KADAR TIMBAL (Pb) PADA LARUTAN PESTISIDA MENGANDUNG TIMBAL - Indriyanti Agustina Putri; Nur Endah Wahyuningsih; Budiyono Budiyono (Jurnal Kesehatan Masyarakat (Undip), 2018)
Agricultural activities use fertilizers and pesticides to optimize agricultural produce. About 99.9% of pesticides used enter and pollute the environment causing health problems. Preliminary test results show that lead levels in agricultural waste and pesticide solutions exceed the specified quality standards. This research aims to find out the effectiveness of manganese greensand with various diameter and thickness to reduce lead content in pesticide solutions. This research uses quasi experiment with control group design. The sample used was an artificial pesticide solution. Data analysis was performed by two way ANOVA test with 95% significancen level. The results showed that the lead level before treatment was 0.238 mg/l. After treatment with manganese greensand with variations in diameter and thickness of lead content decreased, with the highest decrease in variations in diameter of 30 mesh and thickness of 35 cm with a percentage of 52.32%. Based on the two way anova test the p-value is > 0,05, it known that there is no significant difference between treatments. The conclusion of this study is that manganese greensand can reduce lead levels in pesticide solutions with an average of 37.04%, but have not been able to reduce lead levels meet requirment.